PENGARUH METODE DAN ARAH SADAP TERHADAP PRODUKSI GETAH JELUTUNG HUTAN TANAMAN INDUSTRI - Totok K. Waluyo; I. Wahyudi; G. Santosa (Jurnal Penelitian Hasil Hutan, 2012)
Jelutong gum is gum typifies excudates that result from the tapping of Dyera trees, Jelutong giam offers various uses, such as raw material of gom, a misture of automobile tire manufacture, rar material for making paints, adbesives and varnishes, The study was conducted to determine the method and direction of tapping on gum production from Industrial Plantation Forest's Jelutong Trees (HTI) The tapping methods performed are slicing with half spiral pattern from the upper left to the lower right (1/25 Kr Knj. slicing with "V" shape pattern, and slicing with balf-piral pattern from upper right to the lower left (1/25 Ka Kr). The results revealed that HTI of Private Company is a type of swamp (Dyera polyphylla Maj. Mrenis or Dyera lowin Hook f.). The tapping method that afforded the higli gum production and mure applicable was the so-called half-spiral slicing from the upper left toward the lower right (VS Kr King. The properties of jelutong gon prodierd are as follow 46.20% of moisture content, 0.04% of ash content, 0.24% of impurities 0.07% of nitrogen content amt 52.75% of resin.